Universal and Stable Slippery Coatings: Chemical Combination Induced Adhesive‐Lubricant Cooperation. Issue 32 (17th July 2022) - Wang, Dagui; Chen, Yajie; Huang, Yu; Bai, Hao; Tan, Yao; Gao, Pengcheng; Deng, Xu; Xia, Fan; Jiang, Lei
Abstract: Liquid lubricant of low affinity makes slippery coatings widely used in lubricating, anti‐biofouling, anti‐icing, fluid guiding, and drag reduction. Two critical challenges, however, remain in the practical application of slippery coatings consisting of liquid lubricants: (1) universality regardless of roughness and chemical composition of substrates, (2) stability of surface lubricity against evaporation. Herein, a chemical method is reported to create a universal and stable slippery lubricant‐adhesive cooperated coating (SLACC) through acid catalyzed dehydration reaction between the phenolic hydroxyl of polydopamine (PDA), with universal (for challenge‐1) and strong (for challenge‐2) adhesion properties, and liquid‐like polydimethylsiloxane (PDMS), with lubricant properties. Through overlying PDMS on PDA, a spatial gradient interpenetration of chemical combined PDA and PDMS leaving lubricant PDMS at the outermost of coating is achieved. This structure contributes to the following performances of SLACC: nearly universality suitable for 100 different abiotic or biotic substrates and stability sustainable for long‐term usages, UV radiating, refrigerating, hot air drying, freeze drying, knife scratch and abrasion. This proposed strategy is envisioned anti‐fouling from plane to tube and exhibits drag reduction in confined space. Abstract : Spatial distribution, as gradual increase of adhesion proportion from the outermost to the substrate leaving high proportion of lubricant overspreading the outermost, endows a slippery coating with a universal (adapting for 100 substrates), stable (bearing long‐term usage, heating, vacuum, and abrasion), and anti‐fouling (against nanoparticles, chlorella, cells, ants, and snails) properties.